2008
DOI: 10.1167/iovs.07-1477
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Chamber Angle Measurement with Anterior Segment Optical Coherence Tomography: A Comparison between Slit Lamp OCT and Visante OCT

Abstract: Although Visante OCT and SLOCT demonstrate high interobserver reproducibility for anterior chamber angle measurements, their agreement was poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 12 publications
4
87
1
2
Order By: Relevance
“…ARA 500 is the area of the angle recess bounded anteriorly by the AOD 500. (Modified from Figure 2 in Leung et al 17 ) was equally reliable for measurement of the angles. In a study comparing angle measurements between Visante OCT and SL-OCT, the inter-observer coefficient of variation ranged between 4.4 and 7.8%, and between 4.9 and 7.0%, respectively.…”
Section: Reliability Of Anterior Segment Oct For Measurement Of the Amentioning
confidence: 99%
See 3 more Smart Citations
“…ARA 500 is the area of the angle recess bounded anteriorly by the AOD 500. (Modified from Figure 2 in Leung et al 17 ) was equally reliable for measurement of the angles. In a study comparing angle measurements between Visante OCT and SL-OCT, the inter-observer coefficient of variation ranged between 4.4 and 7.8%, and between 4.9 and 7.0%, respectively.…”
Section: Reliability Of Anterior Segment Oct For Measurement Of the Amentioning
confidence: 99%
“…13 Likewise, changes in pupil size and lens position during accommodation of the eye can also influence the evaluation of the angle. Previous studies have shown good repeatability and reproducibility for measurement of AOD, TISA, ARA, and TIA with anterior segment OCT. [14][15][16][17][18] With the lighting condition standardized and the refractive error corrected using an internal fixation target, the intrasession coefficient of variation of the angle width measured with the Visante OCT was r7% and the intersession coefficient variation was r10%. 15 The SL-OCT Figure 2 Measurement of trabecular iris angle (TIA; a), angle-opening distance (AOD; b), trabecular iris space area (TISA; c), and angle recess area (ARA; d).…”
Section: Reliability Of Anterior Segment Oct For Measurement Of the Amentioning
confidence: 99%
See 2 more Smart Citations
“…7,[9][10][11] In addition to TD-OCT systems (Visante, Zeiss; Anterior Segment OCT, Heidelberg, Germany), a dedicated anterior segment FD OCT system is now commercially available (Casia SS-1000, Tomey Corporation, Nagoya, Japan). 12,13 Commercially available posterior segment OCT systems can also be modified to take scans of the anterior segment.…”
Section: Eyementioning
confidence: 99%